2018
DOI: 10.3390/ijerph15010066
|View full text |Cite
|
Sign up to set email alerts
|

The Human Exposure Potential from Propylene Releases to the Environment

Abstract: A detailed literature search was performed to assess the sources, magnitudes and extent of human inhalation exposure to propylene. Exposure evaluations were performed at both the community and occupational levels for those living or working in different environments. The results revealed a multitude of pyrogenic, biogenic and anthropogenic emission sources. Pyrogenic sources, including biomass burning and fossil fuel combustion, appear to be the primary contributors to atmospheric propylene. Despite a very sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 240 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…The source of a fourth factor that predominantly consists of ethene and propene is less clear but can likely be attributed to local vehicular emissions. Prior studies show that vehicle exhaust is a large contributor to urban levels of ethene and propene (Morgott, 2015, 2018), and other source apportionment studies in urban environments have shown that traffic‐related emissions of ethene generally dominate over other outdoor sources (e.g., Morgott, 2015; 2018). Although, we acknowledge that ethene is widely used in the chemical industry, and propene is a raw material for plastics.…”
Section: Resultsmentioning
confidence: 99%
“…The source of a fourth factor that predominantly consists of ethene and propene is less clear but can likely be attributed to local vehicular emissions. Prior studies show that vehicle exhaust is a large contributor to urban levels of ethene and propene (Morgott, 2015, 2018), and other source apportionment studies in urban environments have shown that traffic‐related emissions of ethene generally dominate over other outdoor sources (e.g., Morgott, 2015; 2018). Although, we acknowledge that ethene is widely used in the chemical industry, and propene is a raw material for plastics.…”
Section: Resultsmentioning
confidence: 99%
“…One source of Propylene Oxide in the human body is inhalation of Propylene. PE is an odorless gas that is ubiquitous in the environment, arising from both natural and anthropogenic sources (Morgott 2018). However, the body’s conversion of propylene to propylene oxide appears to reach saturation at high exposure levels (Pottenger 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The body's physiological state influences its handling of propylene. Factors like age, health status, pregnancy and menstruation cycle can alter respiration rate, circulation, liver function and other parameters in ways that change the internal propylene dose and effects (Morgott 2018). For example, higher respiration and circulation during exercise or fever can increase the internal dose.…”
Section: These Results Show That Complex Biological Factors Can Lead ...mentioning
confidence: 99%
See 2 more Smart Citations